Analisis dan Evaluasi Proses Bisnis Menggunakan Business Process Improvement (BPI) pada UB Guest House - Raditya Rizky Putra; Nanang Yudi Setiawan; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
UB Guest House is one of the business unit of Brawijaya University which has responsibility to the Rectorate of Brawijaya University. The running of the business process has a several potential problems that can be hampered to achieve the vision and mission of UB Guest House. The services are not maximal, the system is not integrated, the activities are complex and need a long time, administration and archieving are horrible, they are the problems that founded in the business process at UB Guest House. The Analysis and evaluation are needed to solve the problems and also improvement for the business process. This research uses Business Process Model and Notation (BPMN) Diagrams and Failure Mode and Effect Analysis (FMEA) method for analysis and evaluation business process and also Business Process Improvement (BPI) method for improvement the business process in UB Guest House. The result of this simulation in current business process (as is) and business process recommendation (to be) on reservation and check-in rooms, and check-out rooms have reached 30.15%.